Centennial mussaendas Mussaenda 'Emerlinda R. Roman' and Mussaenda 'Clara L. Davide' - Siar, Simeona V. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2009)
Two new mussaenda varieties were released by the Institute of Plant Breeding, Crop Science Cluster, College of Agriculture, University of the Philippines Los Baños. Mussaenda 'Emerlinda R. Roman', named after the first lady president of the University of the Philippines System, was released in 2008 in celebration of the centennial of the University of the Philippines. It is a selection from the progenies of an open-pollinated Mussaenda 'Dona Esperanza'. It has obovate to round white petaloid surrounded by 6-12 small unexpanded bracts in a cluster similar to a bouquet. Mussaenda 'Clara L. Davide' was released this year (2009) in celebration of the centennial of the University of the Philippines Los Baños. This new mussaenda hybrid was named after the wife of Dr. Romulo G. Davide in recognition of her and Dr. Davide's pivotal role in the successful implementation of the Farmer Scientist Training Project (FSTP) which they initially piloted in Argao, Cebu. The FSTP is now a national program under the Department of Agriculture by virtue of Executive Order (EO) 710. Mussaenda 'Clara L. Davide' is a selection from the progenies of M. 'Doña Esperanza' x 'Doña Aurora'. The cream petaloid has Neyron Rose tinge, edge and vein color. It has one larger bract, obovate to almost round petaloid surrounded by 4-5 small elliptic lanceolate bracts, which twist and turn and surround the true flowers.